2018
DOI: 10.1080/24750263.2018.1480732
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding and faunistic criteria for a revised taxonomy of Italian Ephemeroptera

Abstract: Mayfly (Ephemeroptera) systematics has considerably changed over the years, but many questions have yet to be answered. The synergistic connection between traditional knowledge and new data sources, producing increasingly complex information, has become a compelling issue for modern taxonomy. Molecular tests and the use of reliable reference sequence libraries may constitute effective complements to the traditional method in guiding recognition of species and giving information about taxonomic incongruences wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The Algerian haplotypes present low genetic distance with specimens from southern France, confirming the link for this species between North African and South European populations. The sequences from Sicily, Italy (BP_Gp2) were not assigned to Baetis pavidus with certainty by Tenchini et al (2018) and may represent an undescribed species close to B. pavidus or, alternatively, may be correctly associated with B.…”
Section: Discussionmentioning
confidence: 99%
“…The Algerian haplotypes present low genetic distance with specimens from southern France, confirming the link for this species between North African and South European populations. The sequences from Sicily, Italy (BP_Gp2) were not assigned to Baetis pavidus with certainty by Tenchini et al (2018) and may represent an undescribed species close to B. pavidus or, alternatively, may be correctly associated with B.…”
Section: Discussionmentioning
confidence: 99%
“…Baetislutheri has a wide distribution in the West Palearctic (Bauernfeind and Soldán 2012) but recent molecular analysis has shown that it may constitute a complex of closely related species (Tenchini et al 2018). Koch (1988) reported it from Lebanon and Syria, but these reports may refer to B.golanensis .…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1980s there has been an exponential increase in the number of studies on cryptic species, partly due to the introduction of the PCR, which resulted in the increasing availability of DNA sequences (Bickford et al 2007). Molecular (DNA) methods are valuable in resolving morphologically cryptic lineages and have been used extensively in discriminating species with few or no morphological differences (Jackson and Resh 1998, Rutschmann et al 2014, Leys et al 2016, Tenchini et al 2018. Within the Ephemeroptera, cryptic lineages have been discovered in numerous families through electrophoretic studies (Sweeney and Funk 1991, Zloty et al 1993, Funk and Sweeney 1994 and, more recently, DNA sequence data (Williams et al 2006, Ståhls and Savolainen 2008, Pereira-da-Conceicoa et al 2012.…”
Section: Discussionmentioning
confidence: 99%